Pelatihan Virtual Lab Khusus Pembelajaran Bidang Teknik Untuk Guru SMK Negeri 1 Simpang Katis Guna Mendukung Program Pemerintah Menekan Penularan Covid – 19 - Fahri Setiawan; Muhammad Yonggi Puriza; Welly Yandi; Rudy Kurniawan (Fakultas Teknik, Universitas Bangka Belitung, 2022)
Community service activities carried out was non-research-based community services. The service activity was motivated by Covid-19 pandemic in Indonesia and whole the world. During the Covid-19 pandemic, Minister of Education and Culture Nadiem Anwar Makarim published an online learning policy and forbiden face-to-face meetings and applies to all levels of education. To support limited face-to-face learning and online learning, the Service Team of the Department of Electrical Engineering, University of Bangka Belitung planned to a Virtual Lab Training Special for Engineering Learning for Teachers of SMK Negeri 1 Simpangkatis to Support the Government's Program to Suppress the Transmission of Covid-19. This service has several stages which must be followed starting from collaborating with partners and willingness to become partners, making proposals for community service activities so that they can be funded, conducting training activities and guiding partners in developing Virtual Lab-based technical learning, evaluating and making final reports and targeting one of them to be able to publish in National Journal of Community Service. In the future, with the implementation of this activity, it is hoped that it can become a pilot for the implementation of virtual labs for other SMKs in Central Bangka Regency in particular and the Province of the Bangka Belitung Islands in general.